PENGOLAHAN NILAI RAPORT SISWA SEKOLAH MENGGUNAKAN SISTEM INFORMASI BERBASIS CLOUD COMPUTING - meti nurhayati (Liaison Journal of Engineering, 2022)
Processing school student report cards if not handled properly can cause problems. Problems that arise in processing student report cards are the result of not being careful in processing the data. Data processing that is done manually can pose a risk of errors in entering data. Manual processing using files is also not effective because it takes a relatively longer time. The use of information system-based technology aids is currently very much needed in running a business processing student grades. Based on this information, the following research has been carried out by taking the theme of the use of information technology for the business process of making reports on school students' grades. The system developed in this study uses the PHP programming language and MySQL database. Information technology for this research uses cloud computing-based devices where applications can be run via the internet. Users can interact directly in real time wherever and whenever they are connected to the internet network. This system provides facilities for students, teachers and administrators in processing data on the value of subjects at school including lesson scores, extracurricular activity values and values about students' personalities. The software developed can be a solution for students, teachers in processing data, and making information about report cards on the results of teaching and learning activities in schools.Keywords: System; Information; Mark; Student; Internet, PHP, MySQL